Pengaruh Model Teams Games Tournament Berbantuan Media Flashcard Materi Daerahku Kebanggaanku terhadap Hasil Belajar Siswa SDN Kamal 1 - Nadhyva Maulida Farih; Aditya Dyah Puspitasari (Mataram University, 2026)
This study aimed to examine the effect of the Teams Games Tournament (TGT) learning model assisted by flashcard media on students’ learning outcomes in the “Daerahku Kebanggaanku” material at SDN Kamal 1. The study applied a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The participants consisted of 27 fifth-grade students selected through a saturated sampling technique because the entire population was involved in the study. Data were collected through achievement tests, classroom observations, and documentation. The findings revealed a substantial improvement in students’ learning outcomes after the implementation of the TGT learning model. The average pretest score increased from 48.14 before the treatment to 78.88 after the treatment. Statistical analysis using the paired sample t-test showed that the calculated t-value (9.478) exceeded the t-table value (2.056), while the significance value (Sig. 2-tailed = 0.001) was lower than 0.05, indicating a statistically significant difference between pretest and posttest scores. Furthermore, the N-Gain analysis produced a score of 58%, indicating that the learning model was moderately effective in improving students’ achievement. Observation data also supported these findings, showing excellent implementation of the learning process, with teacher activity reaching 100% and student activity reaching 90%. Therefore, the Teams Games Tournament (TGT) learning model assisted by flashcard media significantly improved students’ learning outcomes and provided an effective learning strategy for elementary school social studies content.